Pandemics and mental health through the lens of literature - Panayi, Adriana C.; Haug, Valentin (The journal of nervous and mental disease, 2021)
Depictions of pandemics presented through the lens of literary authors and poets have everlasting power. In this article, we explore the psychosocial impact of pandemics, as presented through literature and poetry, and attempt to draw similarities with the current COVID-19 pandemic. We explore topics such as fear and anxiety, hopelessness, and suicide ideation. Overall, the psychological devastation caused by epidemics has influenced many major writers and will undoubtedly impact the writers of our generation. These writings are perhaps the richest source of knowledge of humanity's remarkable capacity to endure suffering.
Gesehen am 01.12.2021